Local structural perturbations in HgBa2CuO4+delta - Hyatt, N; Hodges, J; Gameson, I; Hull, S; Edwards, P (1999)
The high-temperature superconduct?or, HgBa2CuO4+δ (δ>0), is the first and arguably the most simple member of the homologous series of mercury-based cuprates, of general formula HgBa2Can-1CunO2n+2+δ (n=1...8). The presence of interstitial oxygen in the HgOδ rock salt layer is crucial in controlling the electronic structure of HgBa2CuO4+δ. Thus, by careful control of the concentration (δ) of interstitial oxygen, one may fine-tune the electronic properties of this material from insulating, through superconducting, to metallic behavior. The local structure adjusts to the presence of interstitial oxygen by displacement of neighboring atoms from their "ideal" positions. We present here a combined powder X-ray and time-of-flight neutron diffraction study of HgBa2CuO4+δ (space group P4/mmm, lattice parameters a=3.8757(1) Å and c=9.4998(1) Å, δ=0.07). From this conjoint approach (powder X-ray and neutron diffraction) we are able to identify the local structural perturbations and atom displacements arising from the occupany (δ=0.07) of the interstitial oxygen site in HgBa2CuO4+δ. © 1999 Academic Press.